Quasi-chemical approximation for polyatomics: Statistical thermodynamics of adsorption - Dávila, M. (2006)
The statistical thermodynamics of interacting polyatomic adsorbates (k-mers) on homogeneous surfaces was developed on a generalization in the spirit of the lattice-gas model and the quasi-chemical approximation (QCA). The new theoretical framework is obtained by combining (i) the exact analytical expression for the partition function of non-interacting linear k-mers adsorbed in one dimension and its extension to higher dimensions, and (ii) a generalization of the classical QCA in which the adsorbate can occupy more than one adsorption site. The coverage and temperature dependence of the Helmholtz free energy, chemical potential, configurational entropy, configurational energy, isosteric heat of adsorption and specific heat are given. The formalism reproduces the classical QCA for monomers, leads to the exact statistical thermodynamics of interacting k-mers adsorbed in one dimension, and provides a close approximation for two-dimensional systems accounting multisite occupancy. Comparisons with analytical data from Bragg-Williams approximation (BWA) and Monte Carlo simulations are performed in order to test the validity of the theoretical model. The resulting thermodynamic description is significantly better than the BWA and still mathematically handable.